2018
DOI: 10.5021/ad.2018.30.6.653
|View full text |Cite
|
Sign up to set email alerts
|

Citron Essential Oils Alleviate the Mediators Related to Rosacea Pathophysiology in Epidermal Keratinocytes

Abstract: Background: Citron is well known for an abundance of antioxidative and anti-inflammatory ingredients such as vitamin C, polyphenol compounds, flavonoids, and limonoids. Objective: In this study, we aimed to evaluate the effects of citron essential oils on rosacea mediators in activated keratinocytes in vitro. Methods: Normal human epidermal keratinocytes (NHEKs) were stimulated with 1α, 25-dihydroxyvitamin D3 (VD3) and interleukin 33 (IL-33) with LL-37 to induce rosacea mediators such as kallikrein 5 (KLK5), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…TRPV1 is expressed on neuronal or non-neuronal cells (e.g., keratinocytes) and play an important role in nociception and neurogenic inflammation 10 11 12 . Therefore, TRPV1 is closely associated with manifestations of rosacea 12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TRPV1 is expressed on neuronal or non-neuronal cells (e.g., keratinocytes) and play an important role in nociception and neurogenic inflammation 10 11 12 . Therefore, TRPV1 is closely associated with manifestations of rosacea 12 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF has been reported to enhance angiogenesis and lymphangiogenesis in rosacea skin, which is also associated with neurovascular dysfunction 15 16 . Moreover, excessive production of LL37 and KLK-5 has also been reported to play a role in the rosacea pathophysiology 11 17 . Rosacea patients have an increased baseline on expression of KLK-5 and LL37, resulting in vasodilatation and leukocyte chemotaxis 11 14 17 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study developed in 2018 (Citron Essential Oils Alleviate the Mediators Related to Rosacea Pathophysiology in Epidermal Keratinocytes), it was demonstrated that citron essential oils have a suppressive effect on LL-37, KLK5, and other pro-inflammatory mediators involved in the pathophysiology of rosacea [ 99 ]. Due to this study, it can now be concluded that citron essential oils may actually normalize the innate immune system response in rosacea patients, and help improve the symptoms in this skin condition.…”
Section: Natural Compounds For the Management Of Rosaceamentioning
confidence: 99%